Brand Love: Role of Online Customer Experience, Value Co-creation, and Relationship Quality - Mustafa, Khurram; Ahmad, Farooq; Qaisar, Muhammad Nawaz; Zada, Shagufta; Jamil, Saqib; Anwer, Naveed; Khawaja, Kausar Fiaz; Vega-Muñoz, Alejandro; Contreras-Barraza, Nicolás; Hamid, Syed Ali Raza; Mariam, Shahida (Frontiers in Psychology, 2022)
Customer experience is a source of retailers' long-term competitive advantage. This study has examined the relationship between online customer experience and brand love through the mechanism of relationship quality in the context of online shopping in Pakistan. The moderating effect of value co-creation on the relationship of online customer experience with relationship quality and brand love has also been examined. Data was collected from a purposive sampling of 189 online customers in an online survey. Results showed that online customer experience significantly impacts customer relationship quality, which leads to brand love. The relationship between online customer experience and relationship quality is found more robust at high levels of value co-creation. However, we observed a significant negative moderating effect of value co-creation on the direct relationship between online customer experience and brand love. It suggests that including customers in the value co-creation process and affording them a pleasurable online shopping experience may be an excellent way to enhance customer relationship quality and brand love. Theoretical and practical implications of these findings are discussed.